Starpreģionu integrācija saistībā ar Dienvidāzijas ekonomiskajiem koridoriem un to ietekmi uz Pakistānas eksporta konkurētspēju. - Awan, Qamber Ali (Latvijas Universitāte, 2016)
Šajā maģistra darbā ir pētīta starpreģionālā integrācija saistībā ar ekonomiskajiem koridoriem īpašu uzsvaru liekot uz Dienvidāzijas reģionu, kur valstis kā Pakistāna, Indija, Bangladeša un Šrilanka ir vienlīdz konkurētspējīgas darbaspēka radīšanā un kaut kādā ziņā preču ražošanā. Ņemot vērā eksportspējas līdzību, šie potenciālie partneri starptautiskajā tirgū konkurē viens ar otru. Maģistra darba mērķis ir izpētīt starpreģionu integrācijas konkrētāk ekonomisko koridoru ietekmi uz Pakistānas eksporta konkurētspēju tekstilizstrādājumu un apģērbu rūpniecību. Darbā apskatītas dažādas pieejas konkurētspējas noteikšanai kā arī Pakistānas tekstilrūpniecības industrijas analīze un ekspertu viedokļi par to.

This study is focused on the economic corridors as way of inter-regional integration in South Asia with the emphasis on a more innovative method of regional integration in South Asia where countries like Pakistan, India, Bangladesh and Sri Lank are equally competitive in producing labour and up to some extent technology intensive manufactured goods. Due to the similarity of exports, these potential regional partners are in a state of competition in the international market The aim of the thesis is to study the influence of inter-regional integration in terms of economic corridors on Pakistan’s export competitiveness in textile and garment industry .The thesis describes different approaches towards competitiveness along with various indicators of competitiveness, the case study of the textile industry of Pakistan and provides the view of experts
Inter-regional integration in terms of economic corridors in South Asia and its impact on the export competitiveness of Pakistan.
Keywords: Vadībzinātne; Economic Corridor; Inter-Regional Integration; Export Competitiveness; Textile industry of Pakistan; South Asia